2021
DOI: 10.1128/jb.00643-20
|View full text |Cite
|
Sign up to set email alerts
|

Sensor Domain of Histidine Kinase VxrA of Vibrio cholerae: Hairpin-Swapped Dimer and Its Conformational Change

Abstract: VxrA and VxrB are cognate histidine kinase (HK) - response regulator (RR) pairs of a two-component signaling system (TCS) found in Vibrio cholerae, a bacterial pathogen that causes cholera. The VxrAB TCS positively regulates virulence, the Type VI Secretion System, biofilm formation, and cell wall homeostasis in V. cholerae, providing protection from environmental stresses and contributing to the transmission and virulence of the pathogen. The VxrA HK has a unique periplasmic sensor domain (SD) and, remarkably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…The VxrA periplasmic domain has been crystallized, and revealed that it has a unique structural fold that forms an uncommon hairpin-swapped dimer. VxrA lacks a cytoplasmic linker region between the second transmembrane helix and the dimerization and histidine phosphotransfer (DHp) domain [51]. Structural studies revealed that the conformational change brought about by the relative rotation of the two monomers in a VxrA-SD dimer might alter the connection of transmembrane helices and, consequently, the pairing of cytoplasmic DHp domains, thereby transferring the ligand-binding signal from the periplasmic SD to the cytoplasmic kinase domain [51].…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…The VxrA periplasmic domain has been crystallized, and revealed that it has a unique structural fold that forms an uncommon hairpin-swapped dimer. VxrA lacks a cytoplasmic linker region between the second transmembrane helix and the dimerization and histidine phosphotransfer (DHp) domain [51]. Structural studies revealed that the conformational change brought about by the relative rotation of the two monomers in a VxrA-SD dimer might alter the connection of transmembrane helices and, consequently, the pairing of cytoplasmic DHp domains, thereby transferring the ligand-binding signal from the periplasmic SD to the cytoplasmic kinase domain [51].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…VxrA lacks a cytoplasmic linker region between the second transmembrane helix and the dimerization and histidine phosphotransfer (DHp) domain [51]. Structural studies revealed that the conformational change brought about by the relative rotation of the two monomers in a VxrA-SD dimer might alter the connection of transmembrane helices and, consequently, the pairing of cytoplasmic DHp domains, thereby transferring the ligand-binding signal from the periplasmic SD to the cytoplasmic kinase domain [51]. It is possible that VxrA and RvvA share similar activation mechanisms as many of the residues important for function in VxrA's sensing domain are conserved in RvvA.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Since VbrK has a TPR-like domain, they assume that a β-lactam antibiotic-sensing protein binds to this domain and activates the VbrK/VbrR system. VxrA HK of Vibrio cholerae, which is homologous to VbrK, is also involved in resistance to β-lactam antibiotics [57]. The crystal structure of the sensor domain of VxrA has been shown to adopt two different packing conformations, suggesting that this conformational change is involved in signal transduction to the cytoplasm.…”
Section: Sensing By Other Structuresmentioning
confidence: 99%
“…The crystal structure of the sensor domain of VxrA has been shown to adopt two different packing conformations, suggesting that this conformational change is involved in signal transduction to the cytoplasm. Similar to VbrK, cavities are observed at the membrane-distal site, but it is unclear whether these are the binding sites for the substrates [57].…”
Section: Sensing By Other Structuresmentioning
confidence: 99%
“…The downstream effectors of this system are well characterized; however, what activates VxrA remains poorly understood. A homologous system in the related bacterium V. parahaemolyticus has been proposed to bind β-lactams directly (18, 19), but strong evidence for this is lacking (20, 21). In addition, it is unlikely that β-lactams are the only activators of VxrAB; other structurally distinct antibiotics, overactive cell wall degradation enzymes, and mechanical stress also activate the system (14, 22).…”
Section: Introductionmentioning
confidence: 99%